Mapping the Landscape of Social Innovation: A Bibliometric Analysis of Key Themes and Trends - Richa Singh Dubey; Tripti Singh (Revista Electronica de Veterinaria, 2024)
Social innovation is an emerging subject attracting scholars' interest due to its societal impact and the growing acceptance of this business model. This article aims to aid academics in developing a theoretical framework and to direct novices in social entrepreneurship research towards relevant journals and authors for their studies. This study employs the Scopus database to identify the research domains with the highest output, the countries and languages contributing predominantly to social innovation research, the inception year of social innovation studies, the journals that publish the majority of this research, and the most significant authors in the field.